Drivers and Barriers Affecting Metaverse Adoption: A Systematic Review, Theoretical Framework, and Avenues for Future Research - Al-Sharafi M.A.; Al-Emran M.; Al-Qaysi N.; Iranmanesh M.; Ibrahim N. (Taylor and Francis Ltd., 2025)
The Metaverse holds immense potential for individuals, organizations, and society, providing immersive and innovative experiences. However, its adoption is a complex process influenced by various factors yet to be thoroughly understood. Therefore, this systematic review aims to identify and classify the drivers and barriers affecting Metaverse adoption. Of the 279 papers gathered from the Web of Science and Scopus databases, 29 studies fulfilled the eligibility requirements and underwent a detailed analysis. The identified factors in the selected studies were classified into distinct categories, including motivational and psychological factors, social factors, technological and Metaverse-related characteristics, learning experience-related factors, inhibitors, privacy and security factors, conditional factors, quality factors, economic-related factors, and personalization and immersion-related factors. We have then proposed a comprehensive Metaverse adoption framework based on this taxonomy to guide future empirical studies. We have also suggested several agendas as a road map for future research on Metaverse adoption. Based on these findings, the review presents several theoretical contributions and practical implications for Metaverse developers and marketers. ? 2023 Taylor & Francis Group, LLC.